Decision Support System Election Municipal Waterworks Customer Class Rates - Muhammad Syaukani; Nia Rizki Ma’rifah (STMIK PONTIANAK, 2020)
The selection of customer class rates in the Banjarmasin City Municipal Waterworks (PDAM) has been made by calculating each indicator value and criteria that have been surveyed by PDAM officers for potential water customers. The calculation is processed in a simple way besides the number of measures assessed so that it requires the time and process of the assessment. To avoid dissatisfaction with potential drinking water customers, a tool in the form of a decision support system is needed. This study aims to develop a decision support system for the customer class rate selection using the Eckenrode and TOPSIS methods. The test was conducted as many as 70 data samples to determine the accuracy and sensitivity of the system developed. The results of the experiment showed that the accuracy value was 95%, and the sensitivity value was 93%. The results of this research conclude that the Eckenrode and TOPSIS methods can be applied both in the development of a decision support system for the customer class rate.